Canine-Assisted Interventions in Hospitals: Best Practices for Maximizing Human and Canine Safety - Barker, Sandra B.; Gee, Nancy R. (Frontiers in Veterinary Science, 2021)
Canine-assisted interventions are becoming more popular in hospital settings, representing a crucial intersection between animals, veterinary medicine, and society. However standardized policies and procedures to minimize risk and maximize benefit to vulnerable humans and protect therapy dog welfare are lacking, posing a challenge to safe practice. Few intervention programs are evaluated to document efficacy compounding the potential risk. This paper presents a rationale for canine-assisted interventions in hospitals and describes the evidence, issues, and challenges to establishing and maintaining safe and effective programs for humans and animals. Recommendations are made for best practices based on the existing scientific evidence and a model program in place in a major medical center for 19 years. Scientific and practical implications are considered